The Subtitling Strategies Applied in The Subtitle of The Movie “The Greatest Showman” from English to Indonesia - Cupu Manik, Ni Nyoman; Made Puspani, Ida Ayu; Mulyawan, I Wayan (Udayana Journal of Social Sciences and Humanities; Vol 8 No 2 (2024): Vol 8 No 2 (2024): UJoSSH, September2024DO - 10.24843/UJoSSH.2024.v08.i02.p02, 2024)
Abstract: In order to conduct a good translation, there are some strategies in subtitling which must be majoring by the subtitler to avoid the misconception. Subtitle strategies that can be applied are expansion, paraphrase, transfer, imitation, transcription, dislocation, condensation, decimation, deletion, and resignation. In this study, “The Greatest Showman” movie is chosen to prove this subtitle strategies theory applied in translating the Indonesian subtitle from English. This study also analyze and describe the translation equivalence finds. This study used documentation method to collect the data and informal presentation methods to present the data analysis. Based on the data collected, it is concluded that Paraphrase is a strategy which frequently used by the translator in the movie. There are many utterances that is translated completely and correctly between the source language and the target language. The second highest subtitling strategy used by the translator is transfer strategy. It is often used because the strategy is supposed to make this subtitle readable and natural in the target audience. Keyword: Translation, Subtitling, Subtitle Strategy, Translation Equivalence.